The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1130/b35097.1
|View full text |Cite
|
Sign up to set email alerts
|

CO2-induced climate forcing on the fire record during the initiation of Cretaceous oceanic anoxic event 2

Abstract: Cretaceous oceanic anoxic event 2 (OAE2) is thought to have been contemporary with extensive volcanism and the release of large quantities of volcanic CO2 capable of triggering marine anoxia through a series of biogeochemical feedbacks. High-resolution reconstructions of atmospheric CO2 concentrations across the initiation of OAE2 suggest that there were also two distinct pulses of CO2 drawdown coeval with increased organic carbon burial. These fluctuations in CO2 likely led to significant climatic changes, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…While the overall trend of the CIE phase reflects global-scale organic carbon burial (e.g., Owens et al, 2018), the concomitant punctuation of isotopically light carbon in both marine and terrestrial biomarkers likely indeed reflects a pulse of isotopically light CO 2 to the ocean-atmosphere system (Figure 6d). While some studies have shown evidence of forest fires in the western US during the middle of the initial CIE (Baker et al, 2019), other studies of the SH#1 core have not shown such evidence (Boudinot & Sepúlveda, 2020), highlighting uncertainties in the sources and extent of such CO 2 pulse at this interval. The similarities in terrestrial biomarker δ 13 C records from the WIS (this study) and the Atlantic basin (Kuypers et al, 1999) with marine biomarkers and resulting pCO 2 estimates (Figure 6d) do support the interpretation of globally increased pCO 2 even during the initial CIE, and ultimately highlights the dynamic nature of the global carbon cycle at the onset of OAE2.…”
Section: Pco 2 From ɛ P Before During and After Oae2mentioning
confidence: 98%
“…While the overall trend of the CIE phase reflects global-scale organic carbon burial (e.g., Owens et al, 2018), the concomitant punctuation of isotopically light carbon in both marine and terrestrial biomarkers likely indeed reflects a pulse of isotopically light CO 2 to the ocean-atmosphere system (Figure 6d). While some studies have shown evidence of forest fires in the western US during the middle of the initial CIE (Baker et al, 2019), other studies of the SH#1 core have not shown such evidence (Boudinot & Sepúlveda, 2020), highlighting uncertainties in the sources and extent of such CO 2 pulse at this interval. The similarities in terrestrial biomarker δ 13 C records from the WIS (this study) and the Atlantic basin (Kuypers et al, 1999) with marine biomarkers and resulting pCO 2 estimates (Figure 6d) do support the interpretation of globally increased pCO 2 even during the initial CIE, and ultimately highlights the dynamic nature of the global carbon cycle at the onset of OAE2.…”
Section: Pco 2 From ɛ P Before During and After Oae2mentioning
confidence: 98%
“…This potentially promotes the rapid growth of plankton that in turn can lead to anoxic lacustrine and oceanic environments (Berrocoso et al, 2010;Kraal et al, 2010;Brown et al, 2012;Liu et al, 2020b). Fire can also supplement the supply of phosphorous through aerosol inputs in the atmosphere as smoke, resulting in phosphorous open ocean deposition (Baker et al, 2020;Yan et al, 2019). Albian marine anoxic events coincided with high atmospheric oxygen levels (estimated about 25%) (Wang et al, 2019b) and the contemporaneous coals in the Hailar Basin contain moderate inertinite levels that suggest periods of frequent wildfire activity.…”
Section: Wildfire and Anoxic Eventsmentioning
confidence: 99%
“…Cretaceous oceanic anoxic events have been widely recognised in the geological record by the occurrence of widespread black shales and carbon isotope excursions in organic-rich and carbonate rocks (Jenkyns, 2010;Jarvis et al, 2011;Baker et al, 2017;Xu et al, 2020a). An apparent increase of wildfire activity inferred by the rise in charcoal abundances (from 189 particles per g/TOM (total organic matter) to 5965 particles per g/TOM) at the initiation of Cretaceous anoxic events has been observed (Baker et al, 2020). Wildfire and associated post-fire erosion have a significant impact on the hydrological cycle through the burning of vegetation and litter layers and the erosion of soil after a rainfall event (Shakesby and Doerr, 2006;Moody et al, 2008;Muir et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This latter was characterized by severe perturbation of the C-cycle, which strongly affected both terrestrial and marine ecosystems (e.g., Jenkyns et al, 2017;Erba, 2018, Frijia et al, 2019;Laurin et al, 2019). However, also the time before the OAE-2 was characterised by climatic instability with frequent temperature, nutrients and other environmental fluctuations (Bottini and Erba, 2018 and reference therein;O Brien et al, 2017;Laurin et al, 2019;Schröder-Adams et al, 2019;Baker et al, 2020). In particular cooling phases before the onset of the OAE 2, have been coupled with high fertility episodes occurred in the oceanic domain (Bottini and Erba, 2018).…”
Section: Early Aptian and Late Cenomanian Chondrodonta Proliferationmentioning
confidence: 99%